Fungal remediation of winery and distillery wastewaters using Trametes pubescens MB 89 and the enhanced production of a high-value enzyme therein - Strong, Peter James (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2008)
In this study white-rot fungi were investigated for their efficiency at distillery wastewater remediation and the production of laccase as a valuable by-product. Distillery wastewaters are high in organic load and low in pH. The presence of phenolic compounds can lead to extremely colour-rich wastewaters and can be toxic to microorganisms. The presence of the inorganic ions may also affect biological treatment. White-rot fungi are unique among eukaryotic or prokaryotic microbes in possessing powerful oxidative enzyme systems that can degrade lignin to carbon dioxide. These ligninolytic enzymes, such as lignin peroxidase, manganese peroxidase and laccase, are capable of degrading a vast range of toxic, recalcitrant environmental pollutants and this makes the white-rot fungi strong candidates for the bioremediation of polluted soils and waters. The laccase enzyme alone has shown remediation potential in wastewaters such as beer production effluent, olive mill wastewater, alcohol distillery wastes, dye-containing wastewaters from the textile industry as well as wastewaters from the paper and pulp industry. It has been shown to be capable of remediating soils and waters polluted with chlorinated phenolic compounds, polyaromatic hydrocarbons, nitrosubstituted compounds and fungicides, herbicides and insecticides.
Keywords: Fungal remediation; Distilleries -- Waste disposal; Wine and wine making -- Waste disposal; Bioremediation Laccase; Enzymes -- Biotechnology